KONSEP BIOPHILIA DALAM PERANCANGAN INTERIOR KAMAR RAWAT INAP STUDI KASUS PUSKESMAS PASAR REBO - Vira Amalia; Raziq Hasan; Made Widyatantri Merati (Jurnal Ilmiah Desain & Konstruksi, 2023)
Health building design often prioritizes physical healing, but ignores the psychological aspect, such as one of them is the design of the inpatient room at the health center. The design of the puskesmas inpatient room generally makes patients feel uneasy and uncomfortable. The impression arising from the atmosphere of the health center, especially in the inpatient room, affects the psychological and physical condition of patients, especially during the healing period. Basically, humans have a tendency to always relate to nature which can have a positive impact on human physical and psychological conditions. This has led to the emergence of the biophilia design approach. Nature In The Space is one of the three categories of biophilia design principles that are considered to be appropriate if applied to the interior design of the puskesmas inpatient room, namely by integrating natural elements into the inpatient room building. With the application of this theme, it is hoped that the patient's anxiety about the health center can be reduced and can accelerate the patient's healing period from a psychological and physical perspective.